The use of device for the body temperature monitoring in clinical practice - Михайлусов, Ростислав Николаевич (ScienceRise: Medical Science, 2016)
Device for the body temperature monitoring was elaborated for the long-term, precise temperature measurement in the given time intervals with further presenting the measurement results in digital form. The aim of research is to elaborate and practically approve in clinical conditions the device for body temperature monitoring. Methods. After analysis of existent analogous devices the technical problem was formulated and device for the body temperature monitoring was manufactured. For realization of the body temperature monitoring the elaborated device was applied in 108 (100 %) wounded persons with fire wounds of the soft tissues. All wounded were of the male sex. The age was from 23 to 58 years. Mean age was 34±4,5 years. Results of research. The temperature indices at the measurement using the mercuric thermometer and elaborated device were not differ in 91 (84,3 %) observations. In 17 (15,7 %) cases were observed the differences in received temperature results not more than by 0,2 0С. At the repeated measurements the differences were not revealed, the previous differences were connected with insufficient contact between the mercuric thermometer and surface of patient’s body. The elaborated device was used in 76 (70,3 %) observations separately, in 32 (29,7 %) observations together with other medical diagnostic devices. The complications, negative phenomena were not observed. Conclusion. At clinical approbation the elaborated method for the monitoring of body temperature of biological objects demonstrated the high reliability of the received results (error of the results 0,1 0С), that allows use device not only for practical but also for scientific aims. The possibility for operative reaction of the medical stuff to alarm as a result of the body temperature rise is convenient